IMPLEMENTING GOOGLE DRIVE–BASED E-PORTFOLIOS IN A FLIPPED ENGLISH CLASSROOM: A QUALITATIVE STUDY OF NURSING STUDENTS’ SPEAKING PERFORMANCE - Bridgita Berlian Budiani; Sri Wuli Fitriati; Widhiyanto; Sri Wahyuni (English Review: Journal of English Education, 2026)
This study qualitatively investigates the implementation of a Google Drive–based e-portfolio in a flipped English classroom, aiming to enhance nursing students’ English for Specific Purposes (ESP) speaking proficiency. The study examines the integration of flipped learning and digital portfolios into instructional practice, considering the communicative demands faced by nursing students in professional healthcare settings. It evaluates student engagement with the learning model and identifies the benefits and challenges that developed during the process. A qualitative research design was utilized, involving twenty sixth-semester nursing students participating in an English for Specific Purposes (ESP) speaking course at a private college of health sciences in Indonesia. Data were gathered from various sources, including recorded speaking samples from students, semi-structured interviews, classroom observations, and survey responses. Thematic analysis yielded four principal findings: noticeable enhancement in speaking performance, heightened engagement and participation in classroom activities, favorable perceptions of Google Drive–based e-portfolios as instruments for practice and reflection, and preliminary challenges concerning adaptation, technology, and time management. The results show that using e-portfolios in a flipped classroom is a structured and useful way to help nursing students improve their professional speaking skills. The study provides pedagogical insights into the practical application of technology-enhanced English for Specific Purposes (ESP) instruction within health sciences contexts.